The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bjid.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Coffee has hepatoprotective benefits in Brazilian patients with chronic hepatitis C even in lower daily consumption than in American and European populations

Abstract: The potential role of coffee as a hepatoprotective substance for chronic liver diseases has been widely discussed. Our main aim was to evaluate the effect of coffee intake regarding clinical, biochemical tests and liver biopsy data in treatment naïve patients with chronic hepatitis C. One hundred and thirty-six patients with chronic hepatitis C, diagnosed through liver biopsy, or by means of clinical, ultrasound or endoscopic signs of cirrhosis, were assessed by determination of biochemical tests, metabolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…Thirty articles underwent full-length review, of which 19 articles were excluded because they were not related to hepatitis C (12 articles), did not have controls or comparison of high versus low caffeine intake (5 articles), was a letter to the editor (1 article), or was an abstract (1 article). Eleven studies were included in the qualitative analysis [16][17][18][19][20][21][22][23][24][25][26], and five studies were included in the meta-analysis [17,[21][22][23][24]. Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty articles underwent full-length review, of which 19 articles were excluded because they were not related to hepatitis C (12 articles), did not have controls or comparison of high versus low caffeine intake (5 articles), was a letter to the editor (1 article), or was an abstract (1 article). Eleven studies were included in the qualitative analysis [16][17][18][19][20][21][22][23][24][25][26], and five studies were included in the meta-analysis [17,[21][22][23][24]. Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Five observational studies (all cross-sectional studies) involving 1507 participants were included in the data Modi et al [23] Costentin et al [17] Machado et al [22] Khalaf et al [21] Oliveira et al [ analysis for the risk of advanced hepatic fibrosis [17,[21][22][23][24]. The pooled OR of advanced hepatic fibrosis in patients who had higher caffeine intake was 0.39 (95% CI: 0.21-0.72) (Fig.…”
Section: Effect Of Caffeine On Hepatic Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been aware of the beneficial effects of coffee on serum liver enzymes and the alcoholic liver disease, but since 2009 several studies have shown that caffeine intake, especially in the form of coffee, has a protective effect on the development of hepatitis C virus (12,14,21,22) . In our previously published study (21) , we observed a reduction in liver fibrosis in patients taking higher doses of caffeine in univariate and multivariate analysis when compared to patients with lower daily intake of caffeine, but did not observe a relationship between caffeine with inflammatory activity in liver biopsy. We drew attention fact that the amount of caffeine necessary to reduce the degree of fibrosis was significantly lower than in English literature (125 mg or only 4 Brazilian cups of coffee versus 250 mg or 308 mg daily).…”
mentioning
confidence: 99%